1991
DOI: 10.2190/qvhr-5fww-74la-f884
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hardiness in the Resolution of Grief

Abstract: Little attention has been paid to personality and its role in resolving grief. This study investigated the relation of the personality factor, hardiness, to resolution of grief. In an anonymous sample of seventy widows, hardiness was a significant predictor of grief resolution in addition to general mental health, time since the death, and the widow's age. Surprisingly, whether the death was expected did not relate to the course of resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Accordingly, numerous studies have illustrated the ability of hardy persons to cope with illnesses and personal loss without belittling the severity of the situation (e.g. Campbell, Swank, & Vincent, 1991;Cohen & Wills, 1985). However, at this point, we cannot make any rm conclusion about the applicability of these appraisal mechanisms to the process of coping with the terror of death.…”
Section: Discussionmentioning
confidence: 90%
“…Accordingly, numerous studies have illustrated the ability of hardy persons to cope with illnesses and personal loss without belittling the severity of the situation (e.g. Campbell, Swank, & Vincent, 1991;Cohen & Wills, 1985). However, at this point, we cannot make any rm conclusion about the applicability of these appraisal mechanisms to the process of coping with the terror of death.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, existing research regarding the psychological construct of hardiness or resiliency has consistently shown that a hardy attitude can work to prevent mental and physical illness (Ouellette, 1993). Specifically, “hardy people…[tend to] feel they can control or influence the events of their experience [and] feel involved or committed to the activities of their life,” and this may provide an extra resource in the struggle to deal with stressors (Campbell, Swank, & Vincent, 1991, p. 54). For example, the ability to maintain a sense of control and commitment during stressful transitions in later life (e.g., retirement, change of residence, health problems) may protect against depressive symptoms (Sandberg & Harper, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…More important, other studies are now claiming that hardiness may serve as a mediator between life stress and mental health as well (Banks & Gannon, 1988;Campbell et al, 1991). These findings are of particular importance to the study of depression and its impact on marital quality in later life.…”
Section: Hardiness Depression and The Quality Of Mature Marriagesmentioning
confidence: 96%